Proteomic analysis of the bone marrow microenvironment in extramedullary multiple myeloma patients - Gregorova, Jana; Vychytilova-Faltejskova, Petra; Kramarova, Tereza; Knechtova, Zdenka; Almasi, Martina; Stork, Martin; Pour, Ludek; Kohoutek, Jiri; Sevcikova, Sabina (Neoplasma, 2022)
Multiple myeloma (MM) is a heterogeneous hematological malignancy characterized by the uncontrolled clonal proliferation of bone marrow (BM) plasma cells. The poor prognosis of patients is associated with the presence of extramedullary disease (EMD). Previously, different mechanisms involved in the colonization of BM niches by MM cells and their escape during EMD have been described. Thus, we aimed to investigate the expression of selected cytokines in the BM plasma of MM patients as well as EMD patients to reveal novel molecules involved in EMD pathogenesis. Expression of 120 different cytokines was measured in BM plasma of 13 MM and 11 EMD patients using Proteome Profiler Antibody Arrays. The correlation between statistically significant cytokines and clinicopathological parameters of patients was determined using the Spearman correlation analysis. Finally, protein-protein interactions were analyzed, and GO and KEGG pathways enrichment analysis was performed. In total, 27 cytokines were found to be differently expressed between MM and EMD patients. After the Benjamini-Hochberg correction for multiple testing, the statistical significance of two cytokines downregulated in EMD (EGF, BDNF) and six cytokines upregulated in EMD (NAP-2, ADIPOQ, CRP, MIG, BAFF, and THBS1) was maintained. Correlation analysis proved a significant association between the expression of these molecules and selected clinical-pathological features of MM/EMD patients. Protein association network analysis revealed important protein-protein interactions between THBS1/EGF, MIG/NAP-2, THBS1/NAP-2, EGF/NAP-2, and ADIPOQ/CRP. Finally, identified cytokines were proved to be significantly involved in focal adhesion, PI3K/AKT, and MAPK signaling pathways, and regulation of cell development, localization, proliferation, migration, differentiation, immune system processes, and stress response. Obtained results confirm the key function of the BM microenvironment in the pathogenesis of MM and indicate the essential role of numerous cytokines in disease progression and EMD development. However, the exact mechanisms need to be further clarified.
Keywords: Humans; Disease Progression; Multiple Myeloma; Proteome; kostní dřeň; mnohočetný myelom; proteom; progrese nemoci; nádorové mikroprostředí; Proteomics; Tumor Microenvironment; lidé; Bone Marrow; proteomika